Integrated Low-Cost Platform for the Capture, Processing, Analysis and Control in Real Time of Signals and Images - Auccahuasi Aiquipa, Wilver (2019)
In the development of projects where hardware and software components are included, electronic components such as sensors, actuators, control mechanisms, artificial vision equipment are used, these require a base platform to be inserted, most of these components require different mechanisms to be used, such as connectors and interfaces, which determines the implementation of a complex system made up of different technologies and communication protocols, added to this problem is the different energy requirements so the system ends up performing a high energy consumption, the proposal presented is the use of the NVIDIA Jetson TK1 development platform, which is equipped with many alternatives to connect a series of sensors and actuators, cameras and other devices, as well as a powerful processing unit graph GPU from where you can perform image processing ny video in the same platform, managing to reduce the size of the solution with a considerable saving in energy consumption, likewise if the solution considers time as a critical factor, it also presents the configuration of being able to work through a time system real, managing to be able to control the access time to the resources of the system and to the devices connected to the development platform. The platform is composed of an ARM Cortex-A15 CPU, an NVIDIA Kepler GPU equipped with 192 CUDA cores, RS232 serial port, UART, GPIO, i2c, as main features.